Characterization and Comparison of Mesoporous Silica Particles for Optimized Drug Delivery - Xinyue Huang; Neil P Young; Helen E Townley (Nanomaterials and Nanotechnology)
In this study we have investigated the suitability of a number of different mesoporous silica nanoparticle structures for carrying a drug cargo. We have fully characterized the nanoparticles in terms of their physical parameters; size, surface area, internal pore size and structure. These data are all required if we are to make an informed judgement on the suitability of the structure for drug delivery in vivo. With these parameters in mind, we investigated the loading/ unloading profile of a model therapeutic into the pore structure of the nanoparticles. We demonstrate that the release can be controlled by capping the pores on the nanoparticles to achieve temporal control of the unloading. We have also examined the rate and mechanism of the degradation of the nanoparticles over an extended period of time. The eventual dissolution of the nanoparticles after cargo release is a desirable property for a drug delivery system.